Micrographic evaluation of different widia compositions of orthodontic pliers submitted to peracetic acid and intensive use - MARCIAL,Érika Zoli (2020)
Abstract Introduction The sterilization and disinfection procedures should be adapted to the chemical profile of the metal alloys present in the instruments. Objective This study aimed to perform a micrographic assessment on the surface characteristics of the widia of orthodontic pliers with two alloy compositions subjected to the action of 0.2% peracetic acid and intensive use. Material and method Twenty distal cutting pliers were divided into two groups (n=10) according to widia composition (%wt): W1- 85% to 87% of tungsten carbide (TC) and other components in the proportion of 13% to 15% and W2 – 87.5% to 88.5% of tungsten carbide and 11.5% to 12.5% for other components. All the pliers were assessed in a stereoscopic magnifying glass (32x) after three treatments: before use (T0); after cutting 100 segments of rectangular stainless-steel wires – intensive use (T1); and after 100 sterilization cycles in 0.2% peracetic acid and intensive use (T2). The cutting sites of all pliers were standardized. Widia regions were defined by line “A” representing T1 and line “B” representing T2. A frequency distribution table and Fisher’s exact test (α=0.05) was performed. We assessed two widia from each composition and treatment in SEM and energy-dispersive X-ray spectroscopy (EDS/SEM). Result The results showed that W1 pliers presented significantly fewer defects after the sterilization cycles with peracetic acid and intensive use than W2 pliers (p=0.0198). There were no differences between both pliers after intensive use (p=1.000). Conclusion The SEM images and EDS analyses showed changes in widia surfaces after the different treatments. Widia composition affected the resistance of the orthodontic pliers after sterilization cycles with 0.2% peracetic acid and intensive use.